The Effect Of Reading Map Through Picture In Powerpoint On The Students’ Achievement In Speaking - Anggraini, Rini (Universitas Muhammadiyah Sumatera Utara, 2023)
This research deals with The Effect of Reading Map Through Picture in PowerPoint on The Students’ Achievement in Speaking. This research was conducted at SMP Muhammadiyah 1 Medan. It was classroom action research by using Reading Map Through Picture in PowerPoint learning and the objective of this research was found out Picture in PowerPoint can make the students’ speaking achievement. The population was the students of the eight grade of SMP Muhammadiyah 1 Medan at 2018/2019 academic year. It was conducted two classes which consisting of 60 students in the class. This research was conducted in experiment class and control class. The technique for collecting data were quantitative. The instruments for collecting data were speaking test as quantitative data and observation sheet, questionnaire sheet. Based on the speaking score. Based on observation sheet, questionnaire sheet, it was found that students were actively involve in speaking process. The result of the research showed that tobserved was higher than t-table (4,2512 2.024) with the level significant 0.05 and Degree of Freedom (DF)= 60. The finding showed that hypothesis of study is accepted. It means that with Reading Map Through Picture in PowerPoint gave a significant effect on students’ speaking achievement.